পদম য়েক্তম লাইরিক (অঙাংগী) - (:unkn) unknown (Memyo Ningombi, Manipuri Language Development Society, 2010)
This is a pictorial primer book for learning Manipuri language, especially designed for children.
Padam Yektam Lairik
Keywords: Manipuri; পদম য়েক্তম লাইরিক (অঙাংগী); Padam Yektam Lairik; Primer; Manipuri; Manipuri